MR Imaging of the Facial Nerve through the Temporal Bone at 3T with a Noncontrast Ultrashort Echo Time Sequence - Guenette, J.P.; Seethamraju, R.T.; Jayender, J.; Corrales, C.E.; Lee, T.C. (American Journal of Neuroradiology, 2018)
SUMMARY: The pointwise encoding time reduction with radial acquisition (PETRA) ultrashort echo time MR imaging sequence at 3T enables visualization of the facial nerve from the brain stem, through the temporal bone, to the stylomastoid foramen without intravenous contrast. Use of the PETRA sequence, or other ultrashort echo time sequences, should be considered in the MR imaging evaluation of certain skull base tumors and perhaps other facial nerve and temporal bone pathologies.CNRcontrast-to-noise ratioIR-FSPGRinversion recovery-prepared fast spoiled gradient recalled-echoPETRApointwise encoding time reduction with radial acquisitionUTEultrashort echo time